2022
DOI: 10.1017/s0263574722000984
|View full text |Cite
|
Sign up to set email alerts
|

Fault diagnosis of robot joint based on BP neural network

Abstract: Aiming at the problem of low accuracy of robot joint fault diagnosis, a fault diagnosis method of robot joint based on BP neural network is designed. In this paper, the UR10 robot is taken as the research object, and the end pose data of the robot are collected in real time. By injecting different joint errors and changing the sampling frequency, the joint fault database is collected and established, and the BP neural network is used for training to obtain the robot neural network fault diagnosis model. The fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Service robots are better adapted to complex environments and meet the essential work needs of human-machine collaborative interaction. Meanwhile, regional differences have brought new requirements to service robots' fault diagnosis, creating more unique service robots [35,76,80,81,87,92]. The main contributions of this review can be concluded as follows: (1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Service robots are better adapted to complex environments and meet the essential work needs of human-machine collaborative interaction. Meanwhile, regional differences have brought new requirements to service robots' fault diagnosis, creating more unique service robots [35,76,80,81,87,92]. The main contributions of this review can be concluded as follows: (1).…”
Section: Discussionmentioning
confidence: 99%
“…In terms of the application of network algorithms, compared to the other two regions, the Asia-Pacific region has employed a more diverse range of network algorithms in robot fault detection. These include Convolutional Neural Networks [76][77][78][79], Back Propagation Neural Networks [80], Deep Residual Networks [35] and Generative Adversarial Networks [81]. Besides, abnormal diagnosis of signals (topic 7) is also a preferred research content in the Asia-Pacific region.…”
Section: Regional Preference Analysismentioning
confidence: 99%
“…There will be no factors such as mechanical wear and deformation to interfere with the results. To compare with similar research [2], the advantages of this research is that the database generated by multiple features of the forward kinematics, which could improve the diagnostic accuracy and classification and, in this way, the features and data fusion methods can be updated according to practical needs.…”
Section: Methodology Overviewmentioning
confidence: 99%
“…With the wide application of informatisation, digitalisation and intelligentisation technologies, the automation level of manufacturing enterprises has been significantly improved, and flexible production lines aiming at rapid automated machining of multispecies precision parts have been proposed, which is of great significance and value for the transformation and upgrading of the manufacturing enterprises' production methods, equipment manufacturing capabilities and product performance [1]. In the processing of flexible production line, it is particularly important to maintain the product quality and quantity, and improve production efficiency, which directly affect the production efficiency and economic benefits of enterprises [2]. In the past decades, a large amount of research has been devoted to production systems, focusing on modelling, performance analysis, bottleneck identification, lean design, product quality inspection and production control of production systems [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation